Pemberdayaan UMKM Halal melalui Kawasan Ekonomi Khusus (KEK) Pekalongan: Meraih Daya Saing Global Melalui Inovasi dan Kolaborasi - Gunawan Aji; Abdillah Dwi Prasetyo; Kausar Faida Rakhman; Grecia Adis Vanessa (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Halal SMEs in Pekalongan need to adopt a more progressive approach to remain relevant and competitive. Innovation is not just a concept but also an urgent necessity to enhance products, production processes, and marketing strategies. Halal SMEs in Pekalongan should view innovation as the key to improving their competitiveness globally. Empowering Halal SMEs through the Pekalongan Halal Special Economic Zone (KEK) should be the main focus in the strategic plan and regional economic development. This research utilizes qualitative descriptive research with an exploratory approach. It is also a type of literature study. The results of this literature review illustrate the importance of empowering Halal SMEs to achieve global competitiveness through innovation and collaboration. In the context of empowerment, crucial aspects include capital, education, training, and financial support, needed to enable SMEs to develop their production capacity and innovation. Furthermore, the Pekalongan Halal KEK plays a significant role as a facilitator of the growth of the halal economic sector. The KEK provides incentives, infrastructure, and strict regulations that encourage transparency and access to the global market for halal products.